Pengaruh Pengungkapan Corporate Social Responsibility Terhadap Corporate Financial Performance Perbankan Yang Terdaftar Di Bursa Efek Indonesia - Denis dan Ignatius Roni Setyawan (Universitas Tarumanagara, 2019)
The purpose of this research is to find out the influence of Corporate Social Responsibility disclosure to the financial performance. The sample used in this study is a banking companies listed on the Indonesia Stock Exchange during the period of 2010 – 2017. As many as 4 banking companies are taken as the research samples by using purposive sampling technique with determined criteria. Based on the result of t test results showed that the variables Corporate Social Responsibility that affect the financial performance. The result of research analysis shows that the implementation of Corporate Social Responsibility has significant positive influence to the financial performance. This condition reflects that the better the activity of Corporate Social Responsibility is done it will result in a better financial performance of the banking companies.